Specific methionine oxidation of cytochrome c in complexes with zwitterionic lipids by hydrogen peroxide: potential implications for apoptosis - Capdevila, Daiana Andrea (2014)
Cytochrome c (Cyt-c) has been previously shown to participate in cardiolipin (CL) oxidation and, therefore,in mitochondrial membrane permeabilization during the early events of apoptosis. The gain in this function has been ascribed to specific CL/Cyt-c interactions. Here we report that the cationic protein Cyt-c is also able to interact electrostatically with the main lipid components of the mitochondrial membranes, the zwitterionic lipids phosphatidylcholine (PC) and phosphatidylethanolamine (PE), through the mediation of phosphate anions that bind specifically to amino groups in the surfaces of protein and model membranes. In these complexes, Cyt-c reacts efficiently with H2O2 at submillimolar levels, which oxidizes the sulfur atom of the axial ligand Met80. The modified protein is stable and presents significantly enhanced peroxidatic activity. Based on these results, we postulate that the rise of H2O2 concentrations to the submillimolar levels registered during initiation of the apoptotic program may represent one signaling event that triggers the gain in peroxidatic function of the Cyt-c molecules bound to the abundant PE and PC membrane components. As the activated protein is a chemically stable species, it can potentially bind and oxidize important targets, such as CL.